Farewell to arms - Cooper, Gary, 1901-1961.; Hayes, Helen, 1900-; Menjou, Adolphe, 1890-1963.; Hemingway, Ernest, 1899-1961.; Borzage, Frank; Glazer, Benjamin F. 1887-1958.; Garrett, Oliver H. P. 1897-1952.; Paramount Publix Corporation; Madacy Video (Firm) (St. Laurent, Quebec, Canada : Madacy Video, 1998)
A wounded American soldier falls in love with his beautiful English nurse during World War I.
Cataloged from credits and American Film Institute Catalog homepage.
Originally released as a motion picture in 1932.
Includes biographical information on Gary Cooper and trivia questions.
Gary Cooper, Helen Hayes, Adolphe Menjou.
DVD format, Dolby digital sound.
Keywords: World War, 1914-1918; American fiction -- 20th century; War films; Feature films